Numerical analysis of the effect of the design of axial-flow pump cannula tip on stagnation and recirculation zones in the left ventricle - M. S. Nosov; G. P. Itkin; V. M. Zaiko; V. A. Malgichev (Вестник трансплантологии и искусственных органов)
Objective: to analyze the inflow cannula of an implantable axial-flow blood pump for a long-term left ventricular assist system in order to minimize thromboembolic complications. Materials and methods. Hemodynamics was considered for 4 different designs of the inflow cannula, from 0 mm to 25 mm long. Areas at the base of the cannula received the most attention. Analysis was performed using the OpenFOAM software. Results. It was revealed that sizes of stagnation and recirculation zones directly depended on the length of the cannula when placed in the left ventricle. Accordingly, longer cannula increases the risk of thrombosis. Conclusion. The design of an inflow cannula determines the likelihood of thrombosis in the cannula. Longer inflow cannula increases stagnation and recirculation zones. This provides a basis for a search for other possible modifications.